Implementation of the Policy for the Implementation of the Bekasi City Regional Health Insurance Program - Ellya Niken Prastiwi; Kamal Alamsyah; Ummu Salamah (Pasundan Social Science Development, 2022)
The main problem in this research is that the policy/program of Regional Health Insurance Based on Family Cards and Population Identification Numbers has not been effectively implemented in Bekasi City. The research method used by the researcher is descriptive analysis with a qualitative research approach. This method and approach was chosen with the consideration that it is hoped that real data can be obtained and are able to examine the research problem in depth so that the expected results can be obtained. The results of the study can be explained that there are factors in implementing the Bekasi City Regional Health Insurance policy, namely standard factors, policy measures and objectives, policy measures and objectives, resources, characteristics of implementing organizations, attitudes of implementers, communication between related organizations and activities. - implementation activities, and the social, economic and political environment. However, in its implementation, these factors have not been fully implemented effectively, namely the policy resource factor and the characteristic factor of the implementing agency so that there are still problems encountered related to the implementation of the Regional Health Insurance policy. This of course also has not been able to provide the best way in providing quality public services, especially with regard to the Regional Health Insurance Program for the Community Based on Family Cards and Population Identification Numbers.